Paradigm Shift toward Reducing Overtreatment of Ductal Carcinoma In Situ of Breast - Sagara, Yasuaki; Julia, Wong; Golshan, Mehra; Toi, Masakazu (Frontiers in Oncology, 2017)
The prevalence of ductal carcinoma in situ (DCIS) of the breast has increased substantially after the introduction of breast cancer screening programs, although the clinical effects of early DCIS detection and treatment remains unclear. The standard treatment for DCIS has involved local breast-conserving surgery followed by radiotherapy (RT) or total mastectomy with/without endocrine therapy, and the choice of local treatment is not usually based on clinicopathologic or biological factors. However, we have investigated the effectiveness of local treatment using breast surgery and RT using Surveillance, Epidemiology, and End Results data, and found that the effectiveness of breast surgery was modified by the nuclear grade. Furthermore, breast cancer-specific survival was identical between patients with low-grade DCIS who did and did not undergo surgery. Moreover, we found that RT after breast-conserving surgery for DCIS was only associated with a survival benefit among patients with risk factors for local recurrence, such as nuclear grade, age, and tumor size. On-going clinical trials and translational research have attempted to develop a treatment strategy that prevents the over-diagnosis and over-treatment of low-risk DCIS, as well as a biology-based treatment strategy for using targeted therapy. Therefore, to develop a tailored treatment strategy for DCIS, we need to identify molecular and biological classifications based on the results from translational research, national databases, and clinical trials.